IMPLEMENTASI PERATURAN GUBERNUR NOMOR 1 TAHUN 2015 TERHADAP PENINGKATAN KINERJA DI LINGKUNGAN BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN DAERAH PROVINSI GORONTALO - Harson Gasim (Publik : (Jurnal Ilmu Administrasi), 2015)
The Performance Accountability of Government that is PAG is the brave policy and radicals had been doing by the Government of Gorontalo province in reforming the system of employee payroll area. PAG policy conducted by classifying the honorariums activities in Regional Government Budget (RGB) that usually received by each apparatus from the level of Governor, the Head of Department until the contract workers or honorary. Furthermore, the posts of honor are changed become the Performance Accountability of Government (PAG) based on the amount which determined by any of variables. The Allowance of Performance Region (PAG) is given in order to improve the welfare of officials based on work performance, place of working, working conditions, and the scarcity of the profession. Giving the Performance Accountability of Government (PAG) in its implementation in the Government of Gorontalo province area Regional Government Budget (RGB) had been brought the changes to improving the quality of service, increase the official performance. Thus, The Performance Accountability of Government (APR) is a noble policy, where in its implementation still requires the support and commitment from the leaders to improve the performance of subordinates and Government Civil Servants (GCS) are always encouraged to give the better service to the society and also to constantly innovate for the preparing of continuous improvement and continuous performance. Giving Performance Accountability of Government (PAG) needs to continue, and followed the sharpen system performance assessment with quantitative indicators that based on professionalism Government Civil Servants (GCS).